2019
DOI: 10.1111/epi.16294
|View full text |Cite
|
Sign up to set email alerts
|

Stereoelectroencephalography electrode placement: Detection of blood vessel conflicts

Abstract: Objective Various forms of vascular imaging are performed to identify vessels that should be avoided during stereoelectroencephalography (SEEG) planning. Digital subtraction angiography (DSA) is the gold standard for intracranial vascular imaging. DSA is an invasive investigation, and a balance is necessary to identify all clinically relevant vessels and not to visualize irrelevant vessels that may unnecessarily restrict electrode placement. We sought to estimate the size of vessels that are clinically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…In studies made on susceptibility weighted imaging (SWI) or digital subtraction angiography (DSA), it appears that trajectories at the vicinity of vessels of a caliber < 1.5 mm in the brain parenchyma (not at the cortical entry) could not be hazardous (65). Other authors suggest that SWI may overestimate the vasculature and thus limit the number of trajectories without influencing the bleeding incidence (66).…”
Section: Seeg Planning Vascular Avoidance and Vascular Complicationsmentioning
confidence: 99%
“…In studies made on susceptibility weighted imaging (SWI) or digital subtraction angiography (DSA), it appears that trajectories at the vicinity of vessels of a caliber < 1.5 mm in the brain parenchyma (not at the cortical entry) could not be hazardous (65). Other authors suggest that SWI may overestimate the vasculature and thus limit the number of trajectories without influencing the bleeding incidence (66).…”
Section: Seeg Planning Vascular Avoidance and Vascular Complicationsmentioning
confidence: 99%
“…Once segmented, 3-D representations of the vascular trees can be generated and considered as structures during automated trajectory planning. 9 This highlights the important difference between vessels that can be seen by the naked eye on the source imaging by the surgeon, compared with those that can be considered and avoided by the automated planning software.…”
Section: Automated Trajectory Planning Considerationsmentioning
confidence: 99%
“…DSA allows vessels less than 1 mm in diameter to be reliably segmented, whereas MR-based modalities are reported to be between 2 mm and 4 mm in diameter. 15 Some studies have shown electrode-vessel conflicts with median vessel diameters less than 1.5 mm do not result in any radiological hemorrhage, 9 , 16 suggesting that they may be clinically insignificant. The implication of considering clinically nonsignificant vasculature is that this may over-restrict SEEG electrode trajectory planning and unnecessarily limit the intracranial sampling.…”
Section: Automated Trajectory Planning Considerationsmentioning
confidence: 99%
“…The reported complication rates after SDE implantations ranged from 5% to 17% per procedure, whereas the complication rate per SEEG procedure was less than 1% 6,7 . Second, the introduction of new radiological and computational innovations and a wide range of navigational image‐guided applications, in addition to new stereotactic methods, allowed for a more convenient and faster depth electrode insertion 5‐6,8,9 . Numerous targets can now be reached in a simplified, more efficient and accurate fashion.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize radiation exposure, especially in the pediatric group, 3T MRI proved to be adequate for most stereotactic procedures 16 . In addition, novel three‐dimensional (3D) computerized models can now further increase the accuracy and safety by automated vessel detection 8 …”
Section: Introductionmentioning
confidence: 99%